Tax Judges' Discretion in Assessing Electronic Evidence as A Legal Loophole in Upholding Justice Based on The Principle of Judicial Independence - Ari Julianto; Faisal Santiago (CV. Green Publisher Indonesia, 2026)
The development of information technology has encouraged the widespread use of electronic evidence in tax disputes, including proceedings before the Tax Court. Although the recognition of electronic evidence within the national legal system has been established through general legislation, these regulations have not been specifically designed to address the procedural requirements of tax law, which is characterized by strict liability and emphasizes legal certainty. This situation grants Tax Judges broad discretion in assessing the validity and evidentiary value of electronic evidence. On the one hand, such discretion is necessary to fill a normative gap; on the other hand, it has the potential to result in inconsistent judicial decisions and legal uncertainty. This study aims to critically analyze the existing normative framework, the judicial practice of assessing electronic evidence, and the implications of Tax Judges' discretion for protecting taxpayers' rights while safeguarding the state's fiscal interests. The research employs a normative legal research method using statutory, conceptual, and case-based approaches. The findings demonstrate that the absence of standardized criteria for assessing electronic evidence has caused judicial discretion to shift from an instrument for achieving justice into a legal loophole that threatens legal certainty. This study proposes an ideal framework for limiting judicial discretion by formulating normative parameters and judicial guidelines that balance the principle of judicial independence with the strict liability nature of tax law. This normative reconstruction is expected to strengthen the consistency of judicial decisions, ensure proportional justice, and enhance public trust in the tax adjudication system.